2021
DOI: 10.1155/2021/4895176
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Stage Optimization Method for the Bearing Layout of Isolated Structure

Abstract: Design of seismic isolated building is often a highly iterative and tedious process due to the nonlinear behavior of the system, a large range of design parameters, and uncertainty of ground motions. It is needed to consider a comprehensive optimization procedure in the design of isolated buildings with optimized performances. This can be accomplished by applying a rigorous optimization technique. However, due to many factors affecting the performance of isolated buildings, possible solutions are abundant, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The properties of triple friction pendulum isolation systems have been optimized by a genetic algorithm (GA) [16][17][18]. Dang et al proposed a two-stage optimization method for parameter and layout optimization of the lead-rubber isolator system [19]. Aceto et al optimized a hybrid isolation system to protect server racks [20].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of triple friction pendulum isolation systems have been optimized by a genetic algorithm (GA) [16][17][18]. Dang et al proposed a two-stage optimization method for parameter and layout optimization of the lead-rubber isolator system [19]. Aceto et al optimized a hybrid isolation system to protect server racks [20].…”
Section: Introductionmentioning
confidence: 99%
“…This measure demands the sum of story translational displacements of the axis to be minimal. Dang et al (2021) developed a two-stage optimization approach for designing isolated buildings incorporating genetic algorithms to identify the optimal parameters of the isolated layer. Almazán and de la Llera (2009) showed that the optimal damper location depends on the static eccentricity and frequency ratio of the bare structure, the total amount of supplemental damping considered, and the frequency content of the excitation.…”
Section: Introductionmentioning
confidence: 99%